2014
DOI: 10.1159/000361051
|View full text |Cite
|
Sign up to set email alerts
|

Carboplatin and Paclitaxel Treatment Is Effective in Advanced Anal Cancer

Abstract: Background: The development of distant metastases of squamous cell carcinoma of the anal canal (SCCA) is rare but has a poor prognosis. A combination of carboplatin and paclitaxel is commonly used for treating squamous cell cancer in different organs, but its efficacy in advanced SCCA is unclear. The objective of this study is to determine the tolerability and outcome of patients with advanced SCCA on carboplatin plus paclitaxel treatment at the Moffitt Cancer Center. Methods: Retrospective analysis was conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 19 publications
4
24
0
3
Order By: Relevance
“…Long‐term outcomes of our patient population were in line with previously reported data . Median overall survival was 14 months, and only 13% of patients were alive 5 years after the diagnosis of advanced disease.…”
Section: Discussionsupporting
confidence: 89%
“…Long‐term outcomes of our patient population were in line with previously reported data . Median overall survival was 14 months, and only 13% of patients were alive 5 years after the diagnosis of advanced disease.…”
Section: Discussionsupporting
confidence: 89%
“…While the majority of patients afflicted with SCCA present with locoregional disease that can be definitively cured with chemoradiation 3,4 , approximately 25% of patients will develop distant metastases 5,6 . Median overall survival for metastatic SCCA is estimated between 15–20 months 7 , and patients are treated most commonly with standard cytotoxic doublet chemotherapy regimens 810 .…”
Section: Introductionmentioning
confidence: 99%
“…However, a United Kingdom randomized trial of chemoradiotherapy for localized disease used a comparable regimen of 5-fluorouracil (5-FU) and mitomycin plus RT failed to demonstrate a reduction in distant metastasis compared to RT alone (17), suggesting the chemotherapy regimen used in our case was highly unlikely to produce a complete response in the overt metastatic disease. In addition, studies of palliative chemotherapy regimens with dose-intense schedules have reported response rates of approximately 50%, with complete response rates in the range of 6-20% (7,18,19). Typical palliative chemotherapy regimens for metastatic SCCA are cisplatin and 5-FU, or carboplatin and paclitaxel (7,8).…”
Section: Discussionmentioning
confidence: 99%